Practicality and potential value of enterprise risk management in the manufacturing sector in China - Zou, X.; Hassan, C.H. (Universiti Putra Malaysia, 2015)
This paper examined the practicality and potential value of Enterprise Risk Management (ERM) in China through three aspects: the impacts of ERM on the relationship between different kinds of risk and whole risk portfolio; the influence of ERM on components of risk structure; and the function of ERM in correlation with risk portfolio and firm performance. A Multiple Indicator Multiple Causes (MIMIC) model was structured for a comprehensive determination of the connection between ERM and firm's performance. The results showed that ERM could reduce the relevance of the kinds of risk to risk portfolio, and the interactions between risk categories are minimised as well. As ERM makes the risk structure more significant to firm's performance, thus, the firm can benefit from risk portfolio and realise profit potentials.